Factors Influencing Consumers’ Level of Acceptance of Goods and Services Tax: A Case Of MBA Students - Hasnah, Haron; Ishak, Ismail; Yuvaraj, Ganesan; Shalene, Kalyanasundaram (2016)
This study examines the factors that influence consumers’ level of acceptance of Goods and Services tax (GST) using the Theory of Planned Behaviour. A total of 228 questionnaires from online survey amongst MBA students from four selected universities, was analysed to achieve the research objectives. The finding reveals that the level of acceptance of GST was low among MBA students, and their attitude towards accepting GST and perceived behavioural control have a significant relationship with the level of acceptance of GST. Further, rule observance behaviour and perception of GST fairness were significant antecedents to attitude and self-efficacy and level of GST knowledge were significant antecedents to perceived behavioural control. The relevant authorities need to draw new mechanisms to enable the public to understand and accept GST.